A localised cloud detection and masking method using spectral analysis - Ahmad, Asmala; Mohd Aboobaider, Burhanuddin; Abdul Ghani, Mohd Khanapi; Razali, Sazalinsyah; Mohamad Is, Saari; Noorazuan, Md. Hashim (American-Eurasian Network for Scientific Information, 2013)
In satellite remote sensing, cloud blocks surface or near surface information. The aim of this study is to investigate the spectral properties of cloud and to carry out cloud detection and masking over Malaysia based on spectral analysis. A cloud detection and masking method tuned to tropical conditions have been developed based on spectral of MODIS (Moderate Resolution Imaging Spectroradiometer) data. Thresholds were applied to three sets of spectral measurements, i.e. reflective bands, thermal bands and brightness temperature difference of thermal bands. The results show that the method was able to detect clouds over Malaysia effectively.